2014
DOI: 10.1080/09593330.2014.988184
|View full text |Cite
|
Sign up to set email alerts
|

Degradation in chlorinated water of the UV filter 4-tert-butyl-4′-methoxydibenzoylmethane present in commercial sunscreens

Abstract: 4-tert-Butyl-4'-methoxydibenzoylmethane (BMDM) is a widely used ultraviolet A filter. In this work, we have studied the effect of chlorine and dissolved organic matter (DOM) concentrations on the stability of UV filter (BMDM) present in two commercial sunscreen cream formulations in water. An experimental design was used to assess the effect of the two experimental factors on the degradation of BMDM. Higher concentrations of chlorine lead to higher degradation percentages of BMDM and higher concentrations of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…The 46 organic UV-filters were grouped in 11 chemical families (Bester, 2007;Crista et al, 2014): benzophenone derivatives (two benzene rings joined by a carbonyl group), p-aminobenzoic acid derivatives (one benzene ring substituted with an amino group and a carboxyl group in the para position), camphor derivatives (organic compounds classified as terpenoids), benzotriazole derivatives (composed by a fused benzene and 5 member unsaturated ring structure with 3 nitrogen atoms), salicylate derivatives (containing a monohydroxybenzoic acid group), triazine derivatives (six-membered benzene-like ring, with three carbons replaced by nitrogen atoms), benzimidazole derivatives (heterocyclic aromatic organic compound derivative with a merged benzene and imidazole ring), cinnamate derivatives (unsaturated carboxylic acids), benzylmalonate derivatives (esters of dicarboxylic acids with a benzylic substituent), crylene derivatives (aromatic acrylates) and dibenzoyl methane derivatives (aromatic 1,3-diketone derivative of acetylacetone, where both methyl groups have been substituted by phenyl groups). Another compound, benzhydrol (diphenylmethanol), was not grouped in any family because it is a metabolite that results from benzophenone reduction.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The 46 organic UV-filters were grouped in 11 chemical families (Bester, 2007;Crista et al, 2014): benzophenone derivatives (two benzene rings joined by a carbonyl group), p-aminobenzoic acid derivatives (one benzene ring substituted with an amino group and a carboxyl group in the para position), camphor derivatives (organic compounds classified as terpenoids), benzotriazole derivatives (composed by a fused benzene and 5 member unsaturated ring structure with 3 nitrogen atoms), salicylate derivatives (containing a monohydroxybenzoic acid group), triazine derivatives (six-membered benzene-like ring, with three carbons replaced by nitrogen atoms), benzimidazole derivatives (heterocyclic aromatic organic compound derivative with a merged benzene and imidazole ring), cinnamate derivatives (unsaturated carboxylic acids), benzylmalonate derivatives (esters of dicarboxylic acids with a benzylic substituent), crylene derivatives (aromatic acrylates) and dibenzoyl methane derivatives (aromatic 1,3-diketone derivative of acetylacetone, where both methyl groups have been substituted by phenyl groups). Another compound, benzhydrol (diphenylmethanol), was not grouped in any family because it is a metabolite that results from benzophenone reduction.…”
Section: Chemistrymentioning
confidence: 99%
“…Inorganic sunscreens, like titanium dioxide and zinc oxide, protect the skin by reflecting and scattering UV radiation (Crista et al, 2014). In this review, only organic UV-filters are considered because of their frequent use at higher quantities.…”
Section: Introductionmentioning
confidence: 99%
“…According to the data presented in Table 6, this substance was moderately removed from conventional WWTPs. The case of avobenzone was further complicated since it forms chloro-metabolites and chlorophenols under disinfection (chlorination, UV-irradiation) [93,94]. These products are generally toxic and little research has been carried out on their environmental fate, mainly on swimming pools and not on WWTP effluents.…”
Section: Resultsmentioning
confidence: 99%
“…In both cases, parent UV filters, providing UV protection, degrade and may lose their photoprotective role. Several studies reported various reactions of UV filters in swimming waters under chlorinated conditions, leading mainly to the formation of chlorinated DBPs, with an emphasis on the determination of primary chlorinated derivatives, or their further degradation [ 21 , 22 , 23 , 24 , 25 ]. Photostability studies showed that dichloro-derivatives in chlorinated waters are less stable than the parent compound, which is not the case for monochloro-derivatives (formed initially) [ 22 ] in the case of BP-3.…”
Section: Introductionmentioning
confidence: 99%